Relationship between Divorce and Well-being among Older Europeans - Giedrius Rupšys; Olga Zamalijeva; Antanas Kairys (Psichologija)
This study explores the relationship between divorce and well-being among older Europeans (50+), utilizing data from eight waves of the Survey on Health, Ageing and Retirement in Europe (SHARE). A quasi-experimental design was used to compare the well-being of divorced older adults before and after divorce with a control group of married individuals. CASP-12 scale was used to assess well-being. Results from a Linear Mixed Model reveal that divorced individuals tend to have lower well-being compared to their married counterparts, likely due to negative outcomes associated with divorce or preexisting lower well-being among those who choose to divorce. However, divorce is not associated with a change in well-being in the 2–3 year period surrounding divorce, potentially due to extended intervals between measurements or the absence of immediate effect of divorce.